1998
DOI: 10.1038/sj.ejcn.1600574
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of muscle protein mass in children with solid tumors by muscle thickness measurement with ultrasonography, as compared with anthropometric methods and visceral protein concentrations

Abstract: Objective: To compare the merits of regional ultrasonography, anthropometry, and measurement of visceral protein concentrations for determining muscle protein mass and nutritional status. Design: Prospective follow-up study. Subjects: Nineteen children (median age 4.7 y, range, 1.4 ±14.1 y) with malignant solid tumors were examined at diagnosis, monthly during preoperative chemotherapy, and 1±2 months after operation; 19 healthy age-and sex-matched children served as controls. Interventions: We measured the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Since chemotherapy is also associated with declines in lean body mass and energy intake 2,3 , maintaining or improving nutrient intake in children undergoing HSCT is an important component of post-transplantation care. Standard practice has suggested energy prescriptions at 130-150% of equation-estimated basal metabolic rate (BMR) 1, 4, 9-11 .…”
Section: Discussionmentioning
confidence: 99%
“…Since chemotherapy is also associated with declines in lean body mass and energy intake 2,3 , maintaining or improving nutrient intake in children undergoing HSCT is an important component of post-transplantation care. Standard practice has suggested energy prescriptions at 130-150% of equation-estimated basal metabolic rate (BMR) 1, 4, 9-11 .…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of arm anthropometric measurement in nutrition algorithms is urged. Femoral quadriceps muscle ultrasonography [5], bioelectrical impedance [6], total body potassium counting [7], and dual energy x-ray absorptiometry scanning [8] have all been used to analyze body composition, but larger studies in groups of children with cancer are lacking.…”
Section: Malnutrition and Chemotherapymentioning
confidence: 99%
“…Taskinen & Saarinen-Pihkala (1998) 23 evaluated the nutritional status of children with solid tumors, at the time of diagnosis and during preoperative and postoperative chemotherapy. They found that the traditional methods (weight-for-height, loss of weight and albumin) for assessing protein energy malnutrition did not detect more than two-thirds of the patients with reduced muscle protein mass, as indicated by muscle thickness ultrasonography.…”
Section: Discussionmentioning
confidence: 99%